A Life of Experimental Economics, Volume I Forty Years of Discovery - Smith, Vernon L. (Springer International Publishing, 2018)
This book provides an intimate history of Nobel Laureate Vernon Smith's early life, combining elements of biography, history, economics and philosophy to show how crucial incidents early in his life provided the necessary framework for his research into experimental economics. Smith takes the reader from his family roots on the railroads and oil fields of Middle America to his early life on a farm in Depression-wracked Kansas. A mediocre student in high school, Smith attended Friends University, on Wichita's west side, where an intense study of mathematics, physics, chemistry, and astronomy enabled him to pass the examinations to enter Caltech and study under luminary scientists like Linus Pauling. Eventually Smith discovered economics and pursued graduate study in the field at University of Kansas and Harvard. This volume ends with his Camelot years at Purdue, where he began his famous work in experimental economics, nurturing his research into an unlikely new field of economics.